2005
DOI: 10.1117/12.600439
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of EUV photoresists with a resist point spread function

Abstract: Extreme ultraviolet (EUV) lithography is under development for possible deployment at the 32-nm technology node. One active area of research in this field is the development of photoresists that can meet the stringent requirements (high resolution, high sensitivity, low LER, etc.) of lithography in this regime. In order to facilitate research in this and other areas related to EUV lithography, a printing station based upon the 0.3-NA Micro Exposure Tool (MET) optic was established at the Advanced Light Source,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Fortunately, an approximate and efficient resist model based on the resist PSF was proposed and has been shown to have good agreement with the experiments' results [9]. This approximate resist model is tailored to the EUV ILT due to its computational efficiency and the analytic form.…”
Section: B Modeling Of the Photoresist Effectmentioning
confidence: 84%
See 2 more Smart Citations
“…Fortunately, an approximate and efficient resist model based on the resist PSF was proposed and has been shown to have good agreement with the experiments' results [9]. This approximate resist model is tailored to the EUV ILT due to its computational efficiency and the analytic form.…”
Section: B Modeling Of the Photoresist Effectmentioning
confidence: 84%
“…An accurate EUV photoresist model is often represented by a complex system of differential equations, making it fairly computationally intensive [2,9]. Fortunately, an approximate and efficient resist model based on the resist PSF was proposed and has been shown to have good agreement with the experiments' results [9].…”
Section: B Modeling Of the Photoresist Effectmentioning
confidence: 97%
See 1 more Smart Citation
“…So, EUVL should be useful for the mass production of ULSI devices with a half pitch (hp) of 45 nm or less. Previous studies [4][5][6] showed that the shapes of resist patterns printed by EUVL were deformed when the pattern size was less than 60 nm. This might be because the performance of the resist and/or projection optics is not high enough.…”
Section: Introductionmentioning
confidence: 98%
“…The modeling of resist properties using a resist point spread function (PSF) was evaluated by measuring the contrast transfer function. 12 The model explains the resolution limit and corner rounding of patterns. Furthermore, it is important that models of flare and resist blur be capable of predicting the CD variation for FVC with proper mask resizing.…”
Section: Introductionmentioning
confidence: 99%